ANALYSIS OF THE PEDAGOGICAL MECHANISMS OF THE EDUCATIONAL PROCESS IN THE FORMATION OF THE ACTIVITY OF TEACHING THE WORLD ENGLISH LANGUAGE - Madina Xasanova (Galaxy International Interdisciplinary Research Journal, 2023)
The article talks about the requirements for issuing documents justifying the correctness of multimedia resources, completeness and completeness of methodical instructions, and instructions for use. In order to create and use multimedia resources, the interface between developers, customers, pedagogues and students, as well as to ensure the ability to master and improve the functionality of multimedia resources, the information of multimedia resources is convenient, and from them allows for repeated use of parts.